(untitled) (Zien Journal of Social Sciences and Humanities, 2024)
This article focuses on aspects considered crucial in editing translations from the Arabic press. Materials from the "Dunyo" news agency were analyzed, examining the role and responsibilities of the editor. For instance, the study investigates aspects that require attention in translating headline ensembles or quotations, as well as in editing facts and realia